Using CADD tools to inhibit the overexpressed genes FAP, FN1, and MMP1 by repurposing ginsenoside C and Rg1 as a treatment for oral cancer - Abouelwafa, Manal; Ibrahim, Tamer M.; El-Hadidi, Mohamed S.; Mahnashi, Mater H.; Owaidah, Amani Y.; Saeedi, Nizar H.; Attia, Hany G.; Georrge, John J.; Mostafa, Amany (Frontiers in Molecular Biosciences, 2023)
Oral cancer is one of the most common cancer types. Many factors could express some genes that cause the proliferation of oral tissues. Overexpressed genes were detected in oral cancer patients; three were highly impacted. FAP, FN1, and MMP1 were the targeted genes that showed inhibition results in silico by ginsenoside C and Rg1. Approved drugs were retrieved from the DrugBank database. The docking scores show an excellent interaction between the ligands and the targeted macromolecules. Further molecular dynamics simulations showed the binding stability of the proposed natural products. This work recommends repurposing ginsenoside C and Rg1 as potential binders for the selected targets and endorses future experimental validation for the treatment of oral cancer.